2021
DOI: 10.1126/sciimmunol.abi8635
|View full text |Cite
|
Sign up to set email alerts
|

Fractionating a COVID-19 Ad5-vectored vaccine improves virus-specific immunity

Abstract: SARS-CoV-2 has caused a global pandemic that has infected more than 230 million people worldwide. Although several vaccine candidates have received emergency use authorization (EUA), there is still limited knowledge on how vaccine dosing affects immune responses. We performed mechanistic studies in mice to understand how the priming dose of an adenovirus-based SARS-CoV-2 vaccine affects long-term immunity to SARS-CoV-2. We first primed C57BL/6 mice with an adenovirus serotype 5 vaccine encoding the SARS-CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 56 publications
5
30
0
Order By: Relevance
“…Moreover, a prominent population of CD4 + and CD8 + memory T cells were biased toward T CM , T EM , and T E subsets through 12 months post-booster vaccination. Research has shown that T EM and T E subsets exhibit rapid cytotoxicity to eliminate the infected cells but tend to be more short-lived than T CM ( 22 ). Conversely, the T CM subset exhibits superior recall capacity ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a prominent population of CD4 + and CD8 + memory T cells were biased toward T CM , T EM , and T E subsets through 12 months post-booster vaccination. Research has shown that T EM and T E subsets exhibit rapid cytotoxicity to eliminate the infected cells but tend to be more short-lived than T CM ( 22 ). Conversely, the T CM subset exhibits superior recall capacity ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that T EM and T E subsets exhibit rapid cytotoxicity to eliminate the infected cells but tend to be more short-lived than T CM ( 22 ). Conversely, the T CM subset exhibits superior recall capacity ( 22 ). Although the classical immunological theory suggests that the inactivated vaccines are not thought to induce CD8 + T-cell responses, our data suggest that the structural integrity of whole SARS-CoV-2 might be the key to elicit antiviral CD8 + memory T-cell responses ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…As positive control, we used sera from mice that received a spike-based adenovirus vaccine (Ad5-S, similar to the CanSino vaccine and the Sputnik vaccine). As expected (Dangi et al ., 2021b; Sanchez et al, 2021), sera from mice that received this spike-based vaccine prevented SARS-CoV-2 infection, even when the sera were diluted 450-fold ( Figure 2B ). However, sera from mice that received the nucleocapsid-based vaccine did not exert any antiviral effect in this in vitro infection assay ( Figure 2B–2C ).…”
Section: Resultsmentioning
confidence: 96%
“…In BALB/c mice, a single mucosal immunization of Ad5 encoding the full-length S protein (Ad5-nCoV) induced robust binding and neutralizing antibody responses and protected the lungs of mice from SARS-CoV-2 infection [22]. In C57BL/6 mice, a low-dose prime (LD, 1 × 10 6 vp) with a standard dose boost (SD, 1 × 10 9 vp) of an Ad5-based vaccine encoding S led to a 72-fold increase in NAbs and superior CD8+ T cell responses compared with the SD/SD regimen [23]. Indeed, this observation aligns with a recent ChAdOx1 nCoV-19 (AZD1222) clinical trial, in which a half-dose prime conferred greater protective efficacy than a standard-dose prime [24].…”
Section: Adenoviral Vectormentioning
confidence: 99%
“…Therefore, there may exist a threshold for the induction of optimal protection, above which vaccinating with higher doses leads to immune exhaustion, and below which vaccinating with lower doses fails to generate sufficient immunity against pathogens. Further, Sanchez et al mechanistically found that lowering the priming dose generated higher central memory CD8+ T cells and fewer exhausted T cells, which underpin dose-sparing as a strategy to improve recall response and vaccine accessibility [23]. In CD-1 mice, a prime-boost immunization of a dual antigen vaccine expressing modified SARS-CoV-2 S and nucleocapsid (N) proteins (hAd5 S-Fusion + N-ETSD) by the subcutaneous route (SC) elicited stronger anti-S IgG2a, IgG2b, and NAb responses compared with hAd5 S-WT; the researchers ascribed the improvement in antibody response to enhanced cell surface expression of S-Fusion [25].…”
Section: Adenoviral Vectormentioning
confidence: 99%